The effect of depression on the thermal nociceptive thresholds in rats with spontaneous pain - Su, Yuan-Lin (Neurosci Bull, 2010)
OBJECTIVE: Recently, there has been growing interest in the interaction between depressive disorders and pain. The purpose of this study was to examine whether depression would lead to a decreased sensitivity to noxious stimuli in rats with spontaneous pain. METHODS: The olfactory bulbectomized rats were used as a model of depression. The depression-like behaviors were assessed by open field test and changes in body weight. Formalin solution was injected into the rat hindpaw to produce ongoing pain. Noxious thermal stimuli were applied onto the hindpaw contralateral to formalin injection, and the withdrawal thresholds were measured. RESULTS: In non-depressive rats, the formalin-treated paw developed hypoalgesia to noxious stimuli while the contralateral paw was not affected. The depressive rats, however, showed a significantly lower sensitivity to noxious thermal stimulus, represented as higher withdrawal thresholds of the contralateral paw, when compared to the non-depressive rats. CONCLUSION: These results demonstrate that depression can alleviate the stimulus-evoked pain even in the context of formalin inflammatory pain, consistent with the previous clinical observations that patients suffering from both depression and persistent pain have decreased sensitivities to noxious experimental stimuli.